The Vestan cataclysm: Impact‐melt clasts in howardites and the bombardment history of 4 Vesta. (27th March 2013) - Cohen, Barbara A.
Abstract: Crystalline impact‐melt samples were created in high‐temperature environments by relatively large craters and, as such, give additional constraints on the nature of the impacts that created them. This article provides new 40 Ar‐ 39 Ar ages of impact‐melt clasts in howardites and shows that these clasts formed on the HED parent body, 4 Vesta, within the time period 3.3–3.8 Ga. Rather than resulting from an increased number of impacts, however, impact‐melted material in howardites may result from unusually high‐velocity impacts occurring in the asteroid belt during this period. This scenario is similar to the late heavy bombardment of the Moon, pointing to an unusual dynamical event at this time across the inner solar system. Therefore, impact‐melt rocks in howardites uniquely record a Vestan cataclysm.